How to Fit Toric Soft Contact Lenses? - Astria Rima Rara Yuswir; Rinda Wati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Refractive error is the first cause of visual impairment and the second cause of vision loss worldwide. Astigmatism is an eye refraction disorder that is characterized by various degrees of refraction in various meridians. Thus, the parallel rays coming into the eye are not focused on one point. One of the treatments is toric soft contact lenses, which is used in astigmatism patients by 47% with astigmatism above 0.75 D. This case report describes the use of toric soft contact lenses using a trial with markers at 6 o'clock, 3 o'clock, and 9 o'clock for the management of regular astigmatism. Case presentation: In this paper, we report 3 cases of patients using toric soft contact lenses. The first patient was a 29-year-old male, the second patient was a 24-year-old female, and the third patient was a 25-year-old male with slowly blurred vision in both eyes and had been wearing glasses. The three cases were classified as moderate astigmatism with a power of 1.25 D and 1.50 D. The patients were given toric soft contact lenses for correction. Contact lens fitting was performed on the patient. Conclusion: Correction of astigmatism can be done by giving glasses, contact lenses, or refractive surgery. If the contact lens axis is suitable, a prescription can be given immediately. If the axis of the toric soft contact lens does not match the available trials, it is necessary to order the size of the toric contact lens according to the astigmatism disorder in the patient's eye.